Uncle Madcap Has a Birthday (José Lezama Lima’s Centennial) - David Curbelo, Jesús (2010)
Because Lezama’s centennial was celebrated in 2010, the Cuban writer pays homage to his fellow countryman through this text, which recounts of Curbelo’s eventual discovery of the works of the author of Paradiso; followed by his amazement as he deciphered, through rigorous study, the elusive codes of Lezama’s poetry as well as the symbolic opulence expressed in his narrative, and how upsetting his essays can be. Curbelo’s reading is a celebration of the totality of Lezama’s literary universe in the continuing deconstruction of the literary genres. As Curbelo points out, his unrelenting and always experimental approach to the works of the Cuban writer is the result of someone who defines himself as “a Lezamian, not a Lezamist, a hue that poses a risk in itself”.